THE TRADITIONAL CHINESE WEDDING PROCESS OF THE HOKKIEN TRIBE IN MEDAN IN THE PRESENT DAY - Vicky Priscilla Salim; Juni Anggraini S (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
Marriage is a historic event in human life that is always eagerly awaited. On that happy day, two hearts that are united want to share their happiness with everyone by celebrating it in a special way. The celebration can be a simple party with only a few dozen guests, or a lavish party attended by hundreds or even thousands of people (Widhardin, 2010). Simple or luxurious, every couple certainly wants their wedding to run smoothly and leave a million memories (Widhardin, 2010). Therefore, to meet their expectations, careful planning is necessary, and a series of preparations need to be carried out. However, busy careers take up more of their time, leaving little left to take care of the various needs of the wedding party: renting a venue, wedding dress, catering, designer, invitations, and so on. Finally, the bride and groom and their respective parents must seek help from other parties. This is where the role of a wedding organizer is needed. This study uses qualitative methods. Data collection was conducted through interviews with several wedding organizers and elders.